Model Arabic Language Teaching for Islamic Senior High Schools/ Ù†Ù…ÙˆØ°Ø¬ Ø¥Ø¯Ø§Ø±Ø© ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ù„Ù…Ø¯Ø§Ø±Ø³ Ø§Ù„Ø«Ø§Ù†ÙˆÙŠØ© - Maskud, Maskud (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Management is the organizational process that involves planning, organizing, leadership and controlling. The research approach used is a qualitative approach with a type of case study with a multisite design in Islamic senior high school in Jember, Indonesia. The analysis technique uses individual case analysis and cross-case analysis. The validity of the data in this study uses a test of credibility, transferability, dependability, and conformability. The findings of this study are (1) Arabic language learning planning model is integrated models, which planning is developed through the integration of the K13 curriculum with the pesantren/ dormitory curriculum. (2) Instructional leadership model in Arabic language learning is participative delegatif and non participative delegatif. Both learning management is carried out centrally with a hierarchical system and a specialization system developed by the teacher (3) The first Arabic language quality control model, input quality control students memorized Taqrib 250 verses and Imriti 250 verses, able to speak Arabic and English, have memorized Al-Quran, MTs, and pesantren. Second, control of the learning process and supported by Arabic language olympiad, student exchanges, LPBA and Yaumul Arabi. Third, control of output based learning IT. The integrative delegated management model of Arabic language learning can improve the quality of students in mastering all Arabic language skills.